2020
DOI: 10.1016/j.chembiol.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Chemoselective Profiling for Mapping Protein Structure

Abstract: Highlights d Deep mutational scanning data are used to guide the generation of protein variants d Parallel chemoselective labeling of variants allows mapping of solvent accessibility d Differences in quantified labeling rates are used to infer structure and dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Moreover, our new approach, ALARM MSPS, provides a method for evaluation of compounds that may function as reversible covalent inhibitors. Recently, a similar assay with isotopic iodoacetamide (IAD) was reported to study protein dynamics, which supports our approach …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, our new approach, ALARM MSPS, provides a method for evaluation of compounds that may function as reversible covalent inhibitors. Recently, a similar assay with isotopic iodoacetamide (IAD) was reported to study protein dynamics, which supports our approach …”
Section: Resultssupporting
confidence: 91%
“…The stereochemistry of the carbon adjacent to the lactam carbonyl was not assigned. 1 (3aR*,9bS*)-3,6-Dimethyl-9-phenyl-1,3a,4,5,7,9b-hexahydro-2H-azuleno [4,5-b]pyrrole-2,8(3H)-dione (59). 59 was prepared according to General Procedure I. Allene-yne 57 (17 mg, 0.061 mmol), rhodium dicarbonyl chloride dimer (3 mg, 0.0061 mmol), and toluene (6 mL) yielded lactam 59 (14 mg, 77% yield) as a white solid after purification by column chromatography (gradient elution with 50−100% ethyl acetate in hexanes).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In 2010, Barbas and co-workers reported a click like reaction for the more abundant tyrosine (Tyr, 3.3% abundance 7 ) using triazolinedione chemistry, 22 after which many applications and refinements for protein conjugation followed. 23–29 Interestingly, when exploring this powerful Tyr click reaction on Trp containing peptides, we observed a high degree of off-target labelling on Trp residues, even in aqueous buffers. In the initial paper reporting the development of the TAD tyrosine click like reaction, Barbas and co-workers reported that the TAD reaction is amino acid selective for tyrosine in aqueous buffers.…”
Section: Introductionmentioning
confidence: 97%
“…HDX-MS of Src was performed as describe in (Potter et al, 2020). Briefly, purified Src 3D (WT or W285T) or Src CD (WT and W285T) was diluted to 0.2 mg/mL in protein dilution buffer (50 mM HEPES, pH 7.8, 150 mM NaCl, 1 mM DTT, 5% glycerol).…”
Section: Hdx-ms Of Srcmentioning
confidence: 99%